Promoting the police: A thematic analysis of the New Zealand Police recruitment campaigns and the construction of officers’ identities - Nairn, Angelique (Journal of criminology, 2022)
Prior to 2021, the New Zealand (NZ) Police had consistently struggled to meet the required target of recruiting new police officers. As a strategy to promote the NZ Police and to subsequently increase the number of officers within the force, a series of recruitment campaigns were broadcasted. Despite appearing to frame the career of a NZ Police officer positively, research has suggested that there is a lack of diversity within the police force with women and ethnic minorities consistently underrepresented, and inequitable working conditions, therefore leading the job to be perceived as unattractive to most. However, after the release of the ?Breaking News? recruitment campaign together with television advertisements and targeted websites outlining information on the recruitment process, the NZ Police successfully met their target with applications exceeding 600 per month. The aim of this research was, therefore, to explore how the identities of NZ Police officers were conceptualised and constructed in the recruitment messaging. A specific focus was how the content in the videos might entice people into considering a role in the force considering the government wanted to increase police numbers by 1800 by 2021. Thematic analysis was applied to 2 NZ Police recruitment videos, 15 ?career path? videos, and 10 ?bring yourself? videos that is accessed through https://www.chatcops.co.nz/. Four key themes were identified which emphasised that the NZ Police are comprised of a diverse group of people, committed to helping the community, prioritising safety and that they are ?normal people? despite their instilled authority.